Penguatan Kebijakan Pengelolaan Sampah Untuk Kota Yang Lebih Berkelanjutan - Nurul Farida; Dinda Sabrina; Nazhar Yoga Ariyanto; Nunun Nurhajati (STISIP Margarana, 2026)
Waste management is a strategic issue in urban development that directly affects public health, environmental quality, and urban sustainability. Rapid population growth and increasing urban activities have led to a continuous rise in waste generation, while management capacity remains limited. This article aims to analyze the implementation of waste management policies and the factors influencing their effectiveness in achieving sustainable cities. The study employs a qualitative descriptive approach through a literature review, examining relevant regulations, academic literature, and previous research. The analysis is based on George C. Edward III’s policy implementation model, which emphasizes communication, resources, implementers’ disposition, and bureaucratic structure. The findings indicate that the effectiveness of waste management policies is strongly determined by consistent policy communication, adequate resources, implementers’ commitment, and institutional coordination. The application of the 3R (Reduce, Reuse, Recycle) strategy and increased community participation are key factors in supporting sustainable urban waste management.